Effects of the pandemic on the performance of students at the National University of Engineering of Peru, according to the socioeconomic profile - Montoya Zavaleta, Modesto Edilberto (2026)
The National University of Engineering (UNI) is renowned for its highly demanding admission exam, which attracts applicants from both private and public schools across various regions of Peru. Between 1950 and 2023, the annual average number of admitted students was 938, with approximately 61% coming from private institutions. This study analyzes the evolution of semester average admission scores according to students’ type of school and admission modality during the period 2015–2023. A rising trend in average scores was observed until the first semester of 2020. Due to the COVID-19 pandemic, no admission exam was held in the second semester of 2020. From 2021 onward, the effects of the pandemic were reflected in a decline in average scores, reaching their lowest point in 2022. However, a slight recovery was recorded in the first semester of 2023, with scores returning to levels comparable to those of the second semester of 2019. Students from private schools obtained slightly higher average scores than those from public schools; nevertheless, this gap gradually narrowed over time. In addition, students admitted through the school-based competition consistently achieved higher averages than those admitted through the regular admission exam, although this pattern was temporarily reversed during the pandemic. The results indicate that the pandemic negatively affected academic performance, highlighting the importance of addressing digital and socioeconomic equity in admission processes and university policies.